English teachers' intention to use flipped teaching: interrelationships with needs satisfaction, motivation, self-efficacy, belief, and support. Issue 8 (2nd November 2022) - Jiang, Lianjiang; Zang, Ning; Zhou, Nan; Cao, Hongjian
Abstract: While the role of flipped teaching in students' language performance is well documented, English teachers' perspective about flipped teaching remains underexplored. Informed by the self-determination theory and the motivation-opportunity-ability theory, this study examined English teachers' intention to use flipped teaching and its interrelationships with fulfillment of needs for competence and autonomy, motivation, self-efficacy, belief, and support in a sample of 166 English teachers in the Chinese EFL context. The findings showed that the teachers had a generally favorable intention to use flipped teaching, with individual variations across gender, universities' prestige, prior experience, and the type of English courses. The results also revealed that needs satisfaction was an antecedent of their use intention for flipped teaching. Identified regulation was related more positively to use intention when the teachers experienced higher self-efficacy and support, whereas external regulation was not associated with use intention when teachers held higher levels of beliefs towards flipped teaching. The findings also showed that introjected regulation was related positively to use intention when the teachers received less supports from their contexts or experienced lower self-efficacy. The findings shed new light on how flipped teaching can be better promoted in language education.